BETWEEN LEGALIZATION AND MORAL HAZARD: A Maslahah-Mafsadah Analysis of Prenuptial Pregnancy Marriage (Kawin Hamil) in Indonesian Islamic Law - Fatarib, Husnul; Hayati, Suci; Ferliadi, Agus Salim (Al-Risalah, 2025)
This study critically examines the implementation of Article 53 of the Compilation of Islamic Law (KHI) in Indonesia, which permits marriage for women who become pregnant out of wedlock (kawin hamil). Using a qualitative case study approach in Lampung, the research draws on in-depth interviews with religious leaders and officials from the Office of Religious Affairs (KUA). It analyzes them through the frameworks of u??l al-fiqh and maq??id al-shar?‘ah. Findings reveal that kawin hamil is widely seen as a necessary socio-legal solution. It protects the child’s lineage (nasab) and preserves family honor (‘irdh). The Hanafi school and aspects of the Sh?fi?? tradition justify this practice. Normatively, it is categorized as a maslahah ?ajiyyah (secondary public interest). However, the study identifies a normative tension. While the policy addresses immediate social concerns, it risks undermining the deterrent function (zajr) of Islamic law against zina (unlawful sexual relations). This creates an imbalance in the pursuit of the higher objectives of Sharia (maq??id al-shar?‘ah). The protection of lineage (?if? al-d?n) and dignity (?if? al-‘irdh) is prioritized over religion in their preventive roles. The study concludes that legal-administrative measures alone are insufficient. It calls for a more holistic policy framework that includes moral counseling, religious education, and a balanced application of maqa?hid principles to uphold both legal certainty and spiritual-moral integrity in Islamic family law.